2010
DOI: 10.1002/ar.21201
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Study on Microvasculature of Left Ventricular Wall in Infant and Adult Yaks

Abstract: Observations on the microvasculature in the left ventricular wall of infant and adult yaks under light and scanning electron microscope (SEM) were presented. Moreover, the diameter of different microvasculature and the density of the capillaries in three layers of the ventricular myocardium were measured using Image Pro-Plus 5.0. The results showed that the average luminal diameter of arterioles and precapillary arterioles in adult yak's hearts were, in most cases, larger than those in infant yaks. On the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Michel et al [26] reported a relationship of 1 capillary to 4 cardiomyocytes in domestic chickens, 1:6 in domestic ducks and 1:9 in pheasants. In the mammalian heart the number of capillaries per mm 2 was reported as about 2000–4000 in the human [27, 28] and rat [29, 30], 5000 capillaries in sheep [31] and 2500 in the Yak [32]. These results indicate the large range of these allied parameters among different species.…”
Section: Discussionmentioning
confidence: 99%
“…Michel et al [26] reported a relationship of 1 capillary to 4 cardiomyocytes in domestic chickens, 1:6 in domestic ducks and 1:9 in pheasants. In the mammalian heart the number of capillaries per mm 2 was reported as about 2000–4000 in the human [27, 28] and rat [29, 30], 5000 capillaries in sheep [31] and 2500 in the Yak [32]. These results indicate the large range of these allied parameters among different species.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was found that the microvasculature and conduction system of the yak heart has unique characteristics [ 20 , 21 ], suggesting that the vasculature of the yak heart constructs an adaptive structure to cope with the low-oxygen situation. However, there is a little information on the levels of protein expression of HIF-1α and VEGF following the birth of yaks, and during their maturation at high altitude.…”
Section: Introductionmentioning
confidence: 99%
“…Six of the studies described precapillary sphincters, two employing TEM [60, 61] and four employing SEM-vc [6266]. In the other studies, the existence of precapillary sphincters was neither mentioned in the text nor demonstrated in the figures; in some studies their absence was concluded.…”
Section: Morphological Observations On the Microvasculaturementioning
confidence: 99%
“…Anderson and Anderson reported an indication of precapillary sphincters in dog heart with SEM-vc [63], but the abrupt interruption and irregular shape of the vascular casts indicated that the resin did not sufficiently fill the vascular lumina so that the identification of precapillary sphincters was not based on sound evidence. He et al [66] reported step-wise constriction of arterioles in yaks and interpreted this as the precapillary sphincters being distributed in a certain section of the arterioles. These structures were far from the precapillary sphincters branching into capillaries reported in the physiological studies.…”
Section: Morphological Observations On the Microvasculaturementioning
confidence: 99%